'Black Duck Feathers' or becoming-perfect. Issue 3 (1st October 2017) - Bucci, Alessandro
This article offers a study of one singular dress created by fashion designer Lee Alexander McQueen, namely, the 'Black Duck Feathers'. Consisting of preternaturally oversized shoulders and hips and of black feathers covering the entire figure, this specific dress emblematically served to turn an indistinct female body into a romantic, yet melancholic black bird of prey. While 'Black Duck Feathers' has been interpreted within the frame of Romanticism in exhibitions at the MET and the V&A, this article makes the dress the starting point of a dialogue between Alexander McQueen's creative process and Deleuze and Guattari's complex philosophical theory of becoming, which they develop in A Thousand Plateaus: Capitalism and Schizophrenia. The aim is to highlight the possibility for an artefact to be a tool for illuminating philosophical theories and concepts and to be the trigger of innumerable and complex considerations. This is in contrast to the way in which critical theory is traditionally used, which is to say, to analyse phenomena, cultural processes and expressions of material culture. The choice of making theory the real object of study in this article is inspired by the very idea of metamorphosis and openness of the body that shapes 'Black Duck Feathers' and that seems to characterize Alexander McQueen's poetics. Metamorphosis of the body, of fields and of theories can be used to study fashion, and is understood here as a way of playing on the edge and among frontiers and as a desire and a need to exceed their borders.